PENGGUNAAN MEDIA RODA KEBERUNTUNGAN PAHLAWANKU PADA MODEL PEMBELAJARAN SFAE TERHADAP HASIL BELAJAR TEMATIK - Khoimah, Nurul; S. Dewi, Endah Rita; Priyanto, Wawan (Elementary School Teacher and Education (PGSD), Faculty of Teacher Training and Education, 2020)
This study aims to determine the effect of the use of wheel of fortune media on learning model the student facilitator and explaining (SFAE) the results of class IV thematic learning at SDN Mangunharjo. This type of research was quantitative with the pre-experimental design. The form of research used is the one-group desaign pretest-posttest. Based on the results of the analysis of the data tested, tcount = 18,207 was obtained. Then compared with the price of the ttable at db = 19 with the level ? = 0.05 is 2.093. The criteria for testing the hypothesis are that Ho is accepted if tcount <ttable. The calculation results obtained by tcount> ttable, so that Ho is rejected and Ha is accepted. This means are differences in the average learning outcomes of the pretest and posttest. Classical learning completeness at posttest is up to 95%, it can be concluded that the wheel of fortune media on the learning model student facilitator and explaining can be improves the learning outcomes of heroic theme for the fourth grade students of SDN Mangunharjo.